Blockchain Technology Adoption among Consumers: An Analysis of Usage Intention and Application Usefulness - Dennis Henning (Junior Management Science (JUMS), 2023)
Blockchain technology research has mainly been focused on general usage intention, mostly examined the organizational perspective, and lacked a differentiated view at specific blockchain applications from the consumer perspective. To foster adoption of blockchain technology, consumer perception of blockchain technology needs further understanding. Building on recent technology adoption literature and employing a representative survey for Germany, we identified context dependent predictors and moderators of blockchain technology usage intention. Results show that drivers of usage intention depend on consumers' age, gender, experience, and cryptocurrency possession. Findings guide practitioners by shedding light on blockchain adoption and usefulness of specific blockchain applications. Moreover, results indicate that blockchain adoption research should be more granular and differentiate between applications and contexts. Our identified specific blockchain applications provide a basis for future research.
Keywords: 650; Blockchain technology; Technology adoption; UTAUT; Usage intention